Modelling and Testing the Dynamic Properties of a Launcher with Unguided Missiles - Zbigniew J. DZIOPA (Modelowanie i badanie dynamicznych właściwości wyrzutni z niesterowanymi pociskami rakietowymi, 2022)
The work analyses the operation of the ZSMU-70 weapon module. The results allowed for the development of several guidelines, aiming to shape the dynamic properties of the WW-4 launcher in order to improve the effectiveness of the ZSMU-70 module. This meant that research was carried out at a military training ground. Unguided NLPR-70 missiles were launched. The launching process was recorded using a Phantom high-speed digital camera. The recorded images were then analysed using TEMA software. Based on the results of empirical research, a physical and mathematical model of the motion was formulated for both the ZSMU-70 module as well as the WW-4 launcher. A computer programme was developed, and the motion of the system was simulated during the launching of the missiles. The results of the theoretical analysis were compared with the analogous results from the empirical research. Having the theoretical model verified, some system parameters were changed, and guidelines were used to improve the effectiveness of the ZSMU-70 weapon module.
Keywords: Dynamika pracy wyrzutni pocisków rakietowych